فاعلية موقع إلكتروني لتعلم معارف ومهارات برنامج الفوتوشوب في تصميم المصنوعات الجلدية النسائية - عبدالفتاح، شيماء عبدالفتاح إبراهيم; خليل، نادية محمود محمد Khalil, Nadiah Mahmoud Mohammed; حربي، سحر حربي محمد (الجمعية العلمية للمصممين, 2022)
يعد برنامج (Adobe Photoshop cc) من برامج الصور النقطية (Bitmap graphics) التي تستخدم لمعالجة الصور والرسوم، ولكن مع التحديثات والتطورات الأخيرة التي تمت إضافتها لآخر إصدارات البرنامج أصبح من الممكن استخدامه في مجال الرسم والتصميم، حيث تم تطوير أدوات الرسم والتلوين مما ساعد على إنتاج رسومات وتصميمات رائعة بدقة عالية وبأقل وقت ممكن، ويتعامل برنامج (Adobe Photoshop cc) مع كل من الصور النقطية (Bitmap) والمتجهات (Victors). وترجع أهمية البحث إلى رفع المستوى المعرفي والمهاري لدى المتدربين في مجال تصميم المصنوعات الجلدية النسائية باستخدام برنامج الفوتوشوب، محاولة التغلب على صعوبة الحصول على البرامج المتخصصة في تصميم المصنوعات الجلدية النسائية وتطويع البرامج غير المتخصصة للقيام بالوظائف التي تؤديها البرامج المتخصصة، تزويد سوق العمل بمصممين تتوافر لديهم القدرة والمهارة على مسايرة التطور التكنولوجي في مجال تصميم المصنوعات الجلدية النسائية، المساهمة في تبنى أساليب تعليمية حديثة في مجال تصميم المصنوعات الجلدية النسائية من خلال تقديم موقع مقترح يمكن استخدامه في التدريب للتعلم الذاتي. وهدف البحث إلى بناء موقع إلكتروني لتعلم معارف ومهارات برنامج الفوتوشوب واستخدامه في تصميم المصنوعات الجلدية النسائية بما يساعد على زيادة الفرص التدريبية وخصوصا في الوقت العصيب الذي تمر به البلاد نظرا لظروف جائحة كورونا بالإضافة إلى رفع قدرة وكفاءة المتدربين من الناحية التصميمية بما يواكب احتياجات سوق العمل، وقياس فاعلية الموقع الإلكتروني واتجاه المتدربين نحو البرنامج التدريبي المرفق على الموقع المقترح. وأتبع البحث المنهج الوصفي التحليلي لدراسة المعارف والمهارات المتضمنة في الموقع الإلكتروني محل الدراسة، والمنهج شبه التجريبي في الدراسة التجريبية للبحث (المجموعة التجريبية الواحدة) والتي تعتمد على الاختبارات القبلية والبعدية، بهدف التعرف على تأثير المتغير المستقل (الموقع الإلكتروني) على المتغير التابع (المستويات المعرفية، المهارية، الوجدانية). وجاءت نتائج البحث تؤكد فاعلية الموقع الإلكتروني المقترح في اكساب المتدربين المعارف والمهارات المتضمنة به، كما أسفرت النتائج عن تكوين اتجاه إيجابي للمتدربين نحو الموقع الإلكتروني المقترح. Adobe Photoshop cc is one of the bitmap graphics programs that are used to manipulate images and graphics, but with the recent updates and developments that have been added to the latest versions of the program, it has become possible to use it in the field of drawing and design, where drawing and coloring tools have been developed, which helped Produce great graphics and designs with high accuracy and in the least possible time, and the program (Adobe Photoshop cc) deals with both bitmap images (Bitmap) and vectors (Victors). Significance: The importance of the research is due to raising the knowledge and skill level of the trainees in the field of designing women’s leather goods using Photoshop, trying to overcome the difficulty of obtaining specialized programs in designing women’s leather goods and adapting non-specialized programs to carry out the jobs performed by specialized programs, providing the labor market with designers that they have The ability and skill to keep pace with the technological development in the field of designing women’s leather goods, contributing to the adoption of modern educational methods in the field of designing women’s leather goods by presenting a proposed site that can be used in training for self-learning. Objectives: The aim of the research is to build a website to learn the knowledge and skills of the Photoshop program and use it in the design of women’s leather goods, which helps to increase training opportunities, especially during the difficult time that the country is going through due to the conditions of the Corona pandemic, in addition to raising the capacity and efficiency of trainees in terms of design in line with the needs of the labor market. And measuring the effectiveness of the website and the trainees' attitude towards the attached training program on the proposed site. Methodology: The research followed the descriptive analytical approach to study the knowledge and skills included in the website under study, and the quasi-experimental approach in the experimental study of the research (one experimental group), which depends on the pre and post tests, with the aim of identifying the impact of the independent variable (website) on the dependent variable (cognitive levels). skill, emotional). The results of the research confirm the effectiveness of the proposed website in providing the trainees with the knowledge and skills contained therein. The results also resulted in the formation of a positive attitude for the trainees towards the proposed website.
Keywords: التعليم الإلكتروني -- الكفاءة التصميمة -- برامج التصميم -- الصناعات النسائية